Supported storytelling through the ‘Life Threads’ approach for family members after traumatic brain injury: “We’ve been through all of this trauma, and you’re giving me some string?” - Charlotte Jane Whiffin; Caroline Ellis-Hill; Alyson Norman; Morag Lee; Parmjeet Kaur Singh; Mark Holloway; Jo Clark-Wilson; Natasha Yasmin; Sara Rose; David Sheffield; Fergus Gracey (PLoS ONE, 2026)
Traumatic brain injury (TBI) brings inevitable and significant changes for family members, yet there is little to relieve their trauma, resolve their grief, or prevent ongoing suffering. The aim of this qualitative pre-feasibility study was to understand the clinical potential of storytelling for families after TBI using the ‘Life Threads’ approach (LTA). An in-depth inductive qualitative design was adopted within an interpretivist paradigm. Following informed consent, participants took part in an online focus group, then engaged with the LTA over four weeks before completing an unstructured, in-person interview. A final focus group explored participants’ reflections on the LTA. A purposive sample of 20 family members began the study, three withdrew after the first focus group leaving a final sample size of 17. The analytical approach used was Braun and Clarke’s reflexive thematic analysis. Eleven participants reported tangible benefits from engaging with the LTA, and thirteen described being able to tell their story in a way not possible through traditional methods. Four main themes were identified: ‘Scaling Cliffs with Broken Wings’ and ‘An Entanglement of Wellbeing’ illustrated the evolving and contextual needs of families post-TBI. ‘Hear Me, See Me: The Power of Story’ highlighted how the LTA facilitated voice, agency, and sense-making, while ‘Creating the Conditions for Stories to Be Told’ identified the enabling environment required for such benefits to emerge. The findings suggest that the LTA offers a meaningful way for family members to explore, express, and make sense of their experiences following TBI. It supports narrative reconstruction, fosters connection and agency, and provides a rare opportunity for self-reflection. However, implementation must be trauma-informed, paced, and supported by skilled facilitators capable of holding space for complex emotional responses.